La autoestima en la superación personal de los niños/as del tercero y cuarto año de educación básica de la Escuela Arcadio Soto Santana en la Parroquia: Vinces, Cantón: Vinces, Provincia: Los Ríos - Vivanco Sanchez, Zaide Patricia (2020)
Self-esteem can be understood as the individual's perception of himself, based on his experiences with others and attributions of his own behavior. It involves emotional, social, physical and academic components. The overcoming can be understood as the expiration of an obstacle or difficulty, or also as the improvement that has taken place in the activity that each person develops, this in terms of the professional and getting more into the personal level, the overcoming, too, it is the improvement that a person can experience in their personal qualities This research will be promoted in scientific concepts, experiences and appropriate techniques that allow nurturing and exercising good self-esteem in schoolchildren, will contain the following thematic blocks based on concepts and ideas of meaning and importance of self-esteem, techniques for their development, overcoming personal and its differentiation with self-esteem.